A Lubricated Nonimmunogenic Neural Probe for Acute Insertion Trauma Minimization and Long‐Term Signal Recording (Adv. Sci. 15/2021). Issue 15 (4th August 2021) - Lee, Yeontaek; Shin, Hyogeun; Lee, Dongwon; Choi, Sungah; Cho, Il‐Joo; Seo, Jungmok
Abstract : Lubricated Immune‐Stealth Probe Surface The practical application of implantable neural probes has been limited due to a negative immune response that deteriorates signal sensitivity over time. In article number 2100231, Il‐Joo Cho, Jungmok Seo, and co‐workers report lubricated immune‐stealth probe surface (LIPS) with non‐immunogenic properties. Near frictionless and anti‐biofouling properties of LIPS reduce acute‐ and chronic‐inflammation, extending neural probe's longevity from 8 to 16 weeks.